The use of radio frequency currents in musculoskeletal injuries - Ciechanowska, Katarzyna (Journal of Education, Health and Sport, 2022)
Electrotherapy is a branch of physical medicine that uses electricity for therapeutic and diagnostic purposes. One of the most modern electrotherapy treatments that uses high frequency currents is Indiba therapy. It is a procedure based on the use of an electric flow of radiofrequency current with a frequency of 448 kHz. Radio frequency currents have become one of the basic methods of treating pain and musculoskeletal injuries. Clinical studies show that therapy with high-frequency currents reduces pain, accelerates blood flow, oxygenates the body and accelerates cell metabolism. In the literature, you can also find articles in which excellent results are presented, such as faster tissue healing and return to physical activity.